A large-scale survey on sharp injuries among hospital-based healthcare workers in China - Gao, Xiaodong (Sci Rep, 2017)
A multi-center survey on sharp injuries (SIs) among hospital-based healthcare workers (HCWs) in seven provinces of China between August and December 2011 was performed. In each province, HCWs from at least 30 hospitals were surveyed by completing a SI report form adapted from the EPINet. The HCWs who declared SIs during the period were interviewed by local infection control practitioners. The survey included 361 hospitals and 206,711 HCWs, most of whom were nurses (47.5%) or doctors (28.4%). In the previous month, 17,506 SI incidents were declared by 13,110 (6.3%) HCWs, corresponding to 1,032 incidents per 1,000 HCWs per year and 121.3 per 100 occupied beds per year. The majority of the SIs was caused by a hollow-bore needle (63.0%). The source patient was identified in 73.4% of all SIs but only 4.4% of all exposures involved a source patient who tested positive for HBV (3.3%), HCV (0.4%) or HIV (0.1%). Only 4.6% of SIs were reported to the infection control team in the hospitals. In conclusion, the rate of SI among HCWs is high in China and SI represents a severe but largely neglected problem. Awareness and safety climate should be promoted to protect the safety of HCWs in China.